Preclinical evidence for pioglitazone and bexarotene combination in oral cancer chemoprevention. Issue 3 (20th December 2021) - Rosas, Rolando R.; Nachbor, Kristine M.; Handley, Nathan; Mathison, Grant; Wuertz, Beverly R.; Ba'th, Fadlullah; Ondrey, Frank G.
Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) requires new treatments and targeted approaches to improve survival. The peroxisome proliferator‐activated receptor γ (PPARγ) and retinoic X receptor alpha (RXRα) nuclear receptor pathways may be targetable with repurposed Food and Drug Administration (FDA)‐approved agents for prevention and treatment. Methods: Oral cancer and leukoplakia cell lines were treated with the PPARγ agonist (pioglitazone) and RXRα activator (bexarotene). PPARγ activation, cellular proliferation, apoptosis activity and phenotype, including the pharmacodynamic marker, involucrin (IVL), were subsequently analyzed using a reporter gene assay, genomic data, MTT assay and western blot. Results: Microarray analysis of HNSCC tumor versus normal tissue shows IVL expression is significantly increased in normal tissue compared to HNSCC tumors ( p  < 0.0001). In MSK Leuk1 and CA 9‐22 cell lines, pioglitazone increases PPARγ DNA binding activity and IVL promoter activity in a dose dependent manner ( p  < 0.01 and p  < 0.0001). Combination treatment with pioglitazone and bexarotene increases PPARγ DNA binding activity and IVL promoter activity ( p  < 0.01 and p  < 0.0001). MTT analysis shows decreases in cell proliferation when cells are treated with pioglitazone and bexarotene. Decreases in cell proliferation are significant to at least p  < 0.05 for all combination versus single agent treatments. Western blot on whole‐cell lysate from cells treated with pioglitazone and bexarotene alone or in combination for IVL showed increased protein levels with combination treatment. Conclusions: Targeting the PPARγ/RXRα heterodimer with pioglitazone and bexarotene was effective in this preclinical project. This was functional in both preneoplastic and oral cancer cell lines. A better understanding of the molecular mechanism on downstream effects on cellular proliferation could potentially have implications clinically, both in oral preneoplasia and possibly head and neck cancer; however, more research needs to be done to explore the potential these medications have in chemoprevention.